Prevalence, Awareness, Treatment and Control of Diabetes Mellitus in a Chinese Population - Yue, Jiqiang; Mao, Xuhua; Xu, Kun; Lü, Lingshuang; Liu, Sijun; Chen, Feng; Wang, Jianming (PLOS ONE, 2016)
Objective The purpose of this study is to evaluate the prevalence, awareness, treatment and glycemic control of diabetes mellitus (DM) in a Chinese population. The findings from this study are expected to offer scientific evidence to better prevent and control the growing number of reported and untreated cases. Methods A cross-sectional survey was conducted in Jiangsu, China. We recruited permanent residents over 18 years of age from eight towns in Jintan (JT) and six towns in Yangzhong (YZ) using a three-stage stratified cluster sampling method. The rates of DM prevalence, awareness, treatment and control as well as their related factors were analyzed. Results A total number of 15404 people were entered into the analysis. The DM prevalence, awareness, treatment and control rates were 7.31%, 58.35%, 51.87% and 14.12%, respectively. Multivariable logistic regression analysis showed that being female was positively related to prevalence (OR = 1.21, 95% CI: 1.07–1.37), awareness (OR = 1.52, 95% CI: 1.19–1.93), treatment (OR = 1.48, 95% CI: 1.17–1.88) and control (OR = 1.87, 95% CI: 1.30–2.67) of DM. Having a family history of diabetes was significantly correlated with DM risk (OR = 1.86, 95% CI: 1.37–2.54) and increased awareness (OR = 3.12, 95% CI: 2.19–4.47), treatment (OR = 3.47, 95% CI: 2.45–4.90) and control (OR = 1.81, 95% CI: 1.22–2.68) of DM. Former smoking status (OR = 1.82, 95% CI: 1.23–2.71), overweight (OR = 2.11, 95% CI: 1.72–2.60) and obesity (OR = 3.46, 95% CI: 2.67–4.50) were related to the risk of DM. Additionally, we found current drinking status to be positively correlated with DM risk (OR = 1.30, 95% CI: 1.01–1.66) and negatively correlated with DM awareness (OR = 0.41, 95% CI: 0.29–0.59) and treatment (OR = 0.41, 95% CI: 0.29–0.59). Our study highlights the high prevalence and inadequate awareness, treatment and control of DM in the Chinese population. Conclusions Management and prevention of DM-related complications should be considered an essential strategy by governments and society. This study assessed the reasons why DM has been increasing and established the first step in determining where to start regarding preventative methods.